2015
DOI: 10.1002/ptr.5331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucosinolates from Turnip (Brassica rapa L.) Root on Bone Formation by Human Osteoblast‐Like MG‐63 Cells and in Normal Young Rats

Abstract: Turnip (Brassica rapa L.) root ethanol extract (TRE) was prepared, and its chemical constituents were characterized by ultra-performance liquid chromatography and mass spectrometry. Thirteen glucosinolates (GSLs) were identified, comprising eight aliphatic, four indolic, and one aromatic compounds. The effects of these GSLs on bone formation were investigated in vitro by incubating human osteoblast-like MG-63 cells with TRE and then analyzing their viability, alkaline phosphatase (ALP) activity, collagen conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Root extracts of horseradish exhibited nematicidal activity against Meloidogyne incognita [ 65 ], while those from turnip ( Brassica rapa L.) had a stimulatory effect in bone formation in rats [ 66 ], while from Bunias erucago showed chemopreventive activity [ 67 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Root extracts of horseradish exhibited nematicidal activity against Meloidogyne incognita [ 65 ], while those from turnip ( Brassica rapa L.) had a stimulatory effect in bone formation in rats [ 66 ], while from Bunias erucago showed chemopreventive activity [ 67 ]…”
Section: Resultsmentioning
confidence: 99%
“…Root extracts of horseradish exhibited nematicidal activity against Meloidogyne incognita [65], while those from turnip (Brassica rapa L.) had a stimulatory effect in bone formation in rats [66], while from Bunias erucago showed chemopreventive activity [67] Sprouts extracts of Raphanus sativus L. induced apoptosis and cytotoxicity in human hepatocarcinoma cells [68] and human breast cancer cells [69]. The sprout extracts of Chinese kale (B. oleracea var.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the analysis performed in this study, it could be concluded that the osteoprotective effect of L. sativum is likely due to a synergistic effect of its various classes of metabolites i.e., alkaloids, lignans, phenolic acids, etc. For example, glucosinolates (peak 10) stimulated bone formation in young rats and in MG-63 cells [ 54 ]. Phenolic acids were also investigated for their osteoprotective effect in ovariectomized rats, with ferulic, caffeic, p -coumaric, and chlorogenic acids to counteract skeletal changes caused by estrogen deficiency in ovariectomized rats [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effects of A. hookeri extracts on human osteoblast-like MG-63 cells were investigated and compared with that of the phytoestrogen daidzein. It had been reported that daidzein is an anabolic agent for bone formation [8,9], and was used as a positive control for a series of in vitro assays by Sugimoto and Yamaguchi [10]. The results of the cell viability assay indicate that EE exerted the highest proliferative effects on MG-63 cells, followed by HWE, while WE had no significant effect on MG-63 cell proliferation.…”
mentioning
confidence: 99%